Chapter Coastal erosion in the Gulf of Follonica and Baratti and coastal defense methods - Bedini, Roberto (Proceedings e report, 2020)
From 1988 to the present the Institute of Marine Biology and Ecology of Piombino has studied the marine environmental situation of the Gulf of Follonica (Italy), in collaboration with the Universities of Siena, Pisa, Urbino, Sassari, Corte (FR) and the CNR of Pisa. In recent years erosion has drastically changed the sandy beaches mainly as a consequence of the constant retreat of the P. oceanica meadows whose possible causes have been studied. Also in the Gulf of Baratti the methods adopted for the defense of the beach have been inadequate.